SOSIALISASI PENCATATAN DAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA BAGI PELAKU UMKM - Finka Fitriany; Prisila Damayanty; Aulia Wildayani; Ibnatul Istinganah; Khoiriyah Nuradilah; Zara Tania Rahmadi (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2023)
This program is carried out with the aim of providing education about recording and preparing financial statements in a simple and easy-to-understand way for UMKM actors, in this case the Ersha Parfum Store. The nature of this community service program is discussion-based socialization / counseling with the aim that the material we convey at the Ersha Parfum Store can be easily understood and answer the problems they experience in recording transactions in the business. The results of the community service program show that the Ersha Parfum Store is interested in slowly changing the way their transactions are recorded in the way we conveyed, because according to them, even with a slightly more recording flow, it is quite easy to read the business situation that occurs more easily. This shows that this service program is enough to increase their insight and interest in the structure of recording and preparing their financial statements.